Postcard from W. Pitts (Los Angeles County Clerk) to the San Luis Obispo County Clerk [front and back] - Los Angeles County Clerk::::::::: (1877)
Postal card addressed to County Clerk, San Louis Obispo Co, California. [illeg.][illeg.]38, Filed Aug 1877, Nathan King, County Clerk[illeg.] [illeg.]